2018
DOI: 10.5539/jas.v10n11p259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline Stress and Calcium Nitrate on Lettuce Grown on Coconut Fiber

Abstract: This study aimed to evaluate the use of saline solutions enriched with calcium nitrate in the production of lettuce grown in coconut fiber. The experiment was carried out from July to August 2017 in a greenhouse, at the Federal Rural University of the Semi-Arid Region (UFERSA), Mossoró-RN, Brazil. A randomized block design was used, in 2 × 5 factorial scheme, with three replicates. Treatments resulted from the combination of two lettuce cultivars [Elba (Curly) and Irene (Crisphead)] and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The treatments were represented by five nutrient solutions (S1 -standard nutrient solution; S2standard nutrient solution + NaCl (3.5 dS m -1 ); S3 -standard nutrient solution + NaCl (3.5 dS m -1 ) + Ca(NO 3 ) 2 (50% = 6.86 mmol L -1 ); S4 -standard nutrient solution + NaCl (3.5 dS m -1 ) + Ca(NO 3 ) 2 (100% = 9.15 mmol L -1 ); S5 -standard nutrient solution + NaCl (3.5 dS m -1 ) + Ca(NO 3 ) 2 (150% = 11.43 mmol L -1 )). The salinity level of irrigation water and the definition of percentages of calcium fertilization were based on the work of Guimarães et al (2017) and Oliveira et al (2018), who also worked with lettuce.…”
Section: Methodsmentioning
confidence: 99%
“…The treatments were represented by five nutrient solutions (S1 -standard nutrient solution; S2standard nutrient solution + NaCl (3.5 dS m -1 ); S3 -standard nutrient solution + NaCl (3.5 dS m -1 ) + Ca(NO 3 ) 2 (50% = 6.86 mmol L -1 ); S4 -standard nutrient solution + NaCl (3.5 dS m -1 ) + Ca(NO 3 ) 2 (100% = 9.15 mmol L -1 ); S5 -standard nutrient solution + NaCl (3.5 dS m -1 ) + Ca(NO 3 ) 2 (150% = 11.43 mmol L -1 )). The salinity level of irrigation water and the definition of percentages of calcium fertilization were based on the work of Guimarães et al (2017) and Oliveira et al (2018), who also worked with lettuce.…”
Section: Methodsmentioning
confidence: 99%
“…This message is initially produced by the roots and, eventually, the Ca 2+ concentration of the shoots decreases which is likely due to the inducible changes of Na + on the amount of Ca 2+ in the cell. Oliveira et al (2018) reported that the interaction between salt stress and calcium nitrate on the number of leaves in lettuce cultivars was significant as the leaf number decreased along with increasing the salinity level, while a foliar application of Ca(NO 3 ) 2 was able to moderate the effect of the salt stress on reducing the leaf number.…”
Section: Interaction Between the Salinity And Calcium Nitrate On The ...mentioning
confidence: 99%
“…Calcium ions maintain the integrity of the plasma membrane in root and shoot cells which are essential for normal cell viability and function (Yarnia et al 2009). Oliveira et al (2018) concluded that the application of calcium nitrate at different levels of salinity stress improved the leaf area index in two lettuce cultivars. In fact, a decrease in the growth and develop- https://doi.org/10.17221/105/2021HORTSCI ment of most plants under salinity may be attributed to a decrease in their leaf area (Munns 2002).…”
Section: Interaction Between the Salinity And Calcium Nitrate On The ...mentioning
confidence: 99%